Earthquake Risk Analysis as a Disaster Mitigation-Based Spatial Planning Strategy in the National Tourism Strategic Area of Kolorai Village, Morotai Island - Marwis Aswan; Sukarmin Idrus; Muhammad Fahmi Aja; Muhammad Risky Tomming (TECHNO: JURNAL PENELITIAN, 2024)
Kolorai Village is a National Strategic Tourism Area (KSPN) influenced by complex tectonic activity. The low community resilience to earthquake disasters in Kolorai Village means that the government must refrain from using disaster risk factors as a reference in developing disaster mitigation-based tourism areas. This research aims to analyse the risk of earthquake disasters in the tourism area of Kolorai Village. Problem-solving in this research uses the survey method and descriptive analysis with a quantitative approach. Primary data or field data in the form of vulnerability and capacity data are obtained using the help of checklist instruments, questionnaires, and interviews. The earthquake disaster risk analysis results in Kolorai Village have a score of 3. They are included in the high category with a percentage of hazard factors of 43%, 28% vulnerability, and 29% capacity. The value of earthquake disaster risk is produced as a map that illustrates the elements of earthquake disaster risk in the Kolorai Village Tourism Area. So that it can be used for spatial planning, it needs to be integrated with disaster risk reduction.